NiCuZn-MgO composite material and preparation method thereof
By using MgO to replace part of NiO in nickel-zinc ferrite materials and adding additives such as Bi2O3, SiO2 and CaO, NiCuZn-MgO composite materials were developed, which solved the problem of high cost of traditional materials, achieved low-cost and high-performance effects, and was suitable for industrial production in the automotive electronics industry.
Patent Information
- Application Number
- CN202411664857.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-20
AI Technical Summary
The price of nickel oxide (NiO), the main component of traditional nickel-zinc ferrite materials, fluctuates greatly, resulting in high cost pressure on the automotive electronics industry chain, limiting the large-scale production and marketization process of products.
Develop a NiCuZn-MgO composite material to reduce material costs by replacing part of NiO with MgO, and optimize the structure and performance of the material by adding additives such as Bi2O3, SiO2 and CaO.
It has achieved the reduction of the overall cost of nickel-zinc ferrite materials, improved the high-frequency performance, mechanical strength and magnetic properties of the materials, is suitable for industrial large-scale production, and improved device efficiency.
Smart Images

Figure BDA0005144341200000061 
Figure BDA0005144341200000071 
Figure BDA0005144341200000081
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of soft ferrite materials, and in particular to a NiCuZn-MgO composite material and a preparation method thereof. Background Art
[0002] With the rapid development and accelerated penetration of the global new energy vehicle industry, new energy vehicles are replacing traditional fuel vehicles at an unprecedented speed. This trend has not only promoted the transformation of the entire automotive industry, but also greatly promoted the continued expansion of the automotive electronics market. Compared with traditional fuel vehicles, new energy vehicles have a higher degree of electrification and a stronger dependence on on-board electronic systems, resulting in a significant increase in the number and complexity of electronic components used in them, especially the value of magnetic components per vehicle has increased several times.
[0003] As the cornerstone of modern automobile intelligence and electrification, automotive electronic technology covers many key components, among which passive electronic components such as inductors play an indispensable role. The core component of the inductor, the inductor core, plays a decisive role in the automotive power management system, inverter, DC / DC converter, and various filtering and power amplifier circuits. It is responsible for processing high-frequency signals, suppressing noise, stabilizing voltage and current, and ensuring the efficient operation of the power system.
[0004] Traditionally, inductor cores are mostly made of nickel-zinc ferrite, which is favored for its excellent magnetic properties, high resistivity and wide operating frequency band. However, the price of nickel oxide (NiO), the main component of nickel-zinc ferrite, fluctuates greatly and remains high, which undoubtedly brings cost pressure to the automotive electronics industry chain and restricts the large-scale production and marketization of related products. Summary of the invention
[0005] In order to solve at least one of the above technical problems, a low-cost nickel-zinc ferrite material with high magnetic permeability and high Bs is developed. The present application provides a NiCuZn-MgO composite material and a preparation method thereof.
[0006] On the one hand, the present application provides a NiCuZn-MgO composite material, including a main component and an additive, wherein the main component includes the following components in weight percentage: Fe2O3 66-76wt%, ZnO 13-16wt%, NiO 6-9wt%, MgO 3-6wt%, and the balance is CuO.
[0007] Based on the total weight of the main component, the additive includes the following components in weight percentage: Bi2O3 0.5-1.5wt%, SiO2 0.3-1.5wt%, CaO 0.3-1.5wt%.
[0008] By adopting the above-mentioned technical scheme, the present application uses MgO to replace part of NiO to reduce the overall cost of nickel-zinc ferrite materials. An appropriate amount of MgO can act as a grain growth inhibitor, which helps to form a fine and uniform grain structure, thereby improving the high-frequency performance and mechanical strength of the material. It can also improve the sintering activity of the ferrite, which is conducive to obtaining better phase purity and higher density, thereby optimizing the magnetic properties; the addition of MgO can improve the sintering behavior of the ferrite, reduce the sintering temperature or shorten the sintering time, and is conducive to industrial large-scale production; the presence of MgO helps to increase the resistivity of the ferrite material, thereby reducing eddy current losses and improving device efficiency.
[0009] This application uses Bi2O3, SiO2 and CaO as additives. Bi2O3, as a grain growth inhibitor, can effectively refine ferrite particles, thereby improving the high-frequency performance of the material; the addition of Bi2O3 can help reduce the sintering temperature of ferrite, and bismuth ions can promote the formation of liquid phase during the sintering process, thereby accelerating the sintering rate and improving the sintering activity; SiO2 can affect the sintering density and microstructure of ferrite, and the dielectric properties and mechanical properties of the material can be improved by adjusting its content; CaO can inhibit the oxidation of grain boundaries and enhance the oxidation resistance and stability of the material.
[0010] Optionally, the main component includes the following weight percentage components: Fe2O3 66-76wt%, ZnO 13-16wt%, NiO 6.5-8wt%, MgO 4-5.5wt%, and the balance is CuO; Optionally, in the main component, the weight ratio of NiO to MgO is 1.2 to 2:1.
[0011] Optionally, in the main component, the weight ratio of NiO to MgO is 1.5:1.
[0012] In a second aspect, the present application provides a method for preparing the above-mentioned NiCuZn-MgO composite material, comprising the following steps: S1, mixing the main components Fe2O3, ZnO, NiO, MgO, CuO and part of Bi2O3 in the additive by wet sand grinding to obtain a mixture A; S2, pre-calcining the mixed material A obtained in step S1 to obtain a pre-calcined material; S3, adding additives SiO2, CaO and the remaining part of Bi2O3 to the pre-burned material obtained in step S2, and performing secondary sand grinding to obtain a mixed material B; S4, adding a binder and a defoamer to the mixed material B obtained in step S3, stirring and mixing, and then spraying and granulating to obtain a granular material; S5, pressing the granular material obtained in step S4 into a green body through a mold; S6, sintering the green body obtained in step S5, and after sintering, rapidly cooling to obtain the NiCuZn-MgO composite material.
[0013] By adopting the above technical scheme, the present application pre-sinters the main component and part of Bi2O3 by mixed sand grinding, and then adds all the additive parts including the remaining Bi2O3 by secondary sand grinding. Adding Bi2O3 twice can significantly optimize the structure of high nickel zinc ferrite, make the grains more uniform, and significantly improve the density of nickel zinc ferrite, so that the nickel zinc ferrite obtains high strength.
[0014] The preparation method of the NiCuZn-MgO composite material of the present application is simple and suitable for industrial production.
[0015] Optionally, in step S1, the amount of Bi2O3 added is 0.3-0.5wt%, and the sand grinding time is 1-2h.
[0016] Optionally, in step S2, the pre-burning temperature is 800-900° C., and the pre-burning time is 3-4 hours.
[0017] Optionally, in step S3, a dispersant is added in an amount of 0.5 to 1.2% by weight of the total weight of the main components.
[0018] Optionally, the dispersant comprises mannitol, light calcium carbonate and sodium dodecyl sulfate in a weight ratio of (1-3):(5-7):(1-3).
[0019] By adopting the above technical solution, the present application adds a dispersant during sand grinding, and through the joint action of mannitol, light calcium carbonate and sodium dodecyl sulfate, the dispersibility and sand grinding effect of the ferrite raw material can be significantly improved, and the particle distribution can be made more uniform. Mannitol and light calcium carbonate promote particle refinement through steric hindrance effect and adsorption, while sodium dodecyl sulfate further improves dispersibility through electrostatic repulsion effect.
[0020] Optionally, after the secondary sand grinding in step S3, the particle size D50 of the mixture B is 0.9±0.1 μm.
[0021] Optionally, in step S4, the binder is a PVA binder, and the amount of the PVA binder added is 0.1-0.3wt% of the solid content of the mixture B; the defoaming agent is polydimethylsiloxane, and the amount of the polydimethylsiloxane added is 0.05-0.15wt% of the solid content of the mixture B.
[0022] Optionally, in step S6, the sintering temperature is 1050-1100° C., and the sintering time is 5-6 hours.
[0023] In summary, the present invention includes at least one of the following beneficial technical effects: 1. The use of MgO to replace part of NiO in the present application can reduce the overall cost of nickel-zinc ferrite materials. An appropriate amount of MgO can act as a grain growth inhibitor, which helps to form a fine and uniform grain structure, thereby improving the high-frequency performance and mechanical strength of the material. It can also improve the sintering activity of the ferrite, which is conducive to obtaining better phase purity and higher density, thereby optimizing the magnetic properties; the addition of MgO can improve the sintering behavior of the ferrite, reduce the sintering temperature or shorten the sintering time, and facilitate industrial large-scale production; the presence of MgO helps to increase the resistivity of the ferrite material, thereby reducing eddy current losses and improving device efficiency.
[0024] 2. This application uses Bi2O3, SiO2 and CaO as additives. Bi2O3, as a grain growth inhibitor, can effectively refine ferrite particles, thereby improving the high-frequency performance of the material; the addition of Bi2O3 can help reduce the sintering temperature of ferrite, and bismuth ions can promote the formation of liquid phase during the sintering process, thereby accelerating the sintering rate and improving the sintering activity; SiO2 can affect the sintering density and microstructure of ferrite, and by adjusting its content, the dielectric properties and mechanical properties of the material can be improved; CaO can reduce grain boundary resistance and improve magnetic permeability, and can also inhibit the oxidation of grain boundaries, enhancing the oxidation resistance and stability of the material.
[0025] 3. In the present application, the main component and part of Bi2O3 are mixed and sand-milled for pre-sintering, and then all the additives including the remaining Bi2O3 are added after a second sand-milling. Adding Bi2O3 twice can significantly optimize the structure of high nickel-zinc ferrite, make the grains more uniform, and significantly improve the density of nickel-zinc ferrite, thereby enabling the nickel-zinc ferrite to obtain high strength.
[0026] 4. The preparation method of the NiCuZn-MgO composite material of the present application is simple, the product has good stability, and is suitable for industrial production. DETAILED DESCRIPTION
[0027] The present application is further described in detail below in conjunction with embodiments.
[0028] The present application designs a NiCuZn-MgO composite material, including a main component and an additive, wherein the main component includes the following weight percentage components: Fe2O3 66-76wt%, ZnO 13-16wt%, NiO 6-9wt%, MgO 3-6wt%, and the balance is CuO; The additive is calculated based on the total weight of the main component, and includes the following weight percentage components: Bi2O3 0.5-1.5wt%, SiO2 0.3-1.5wt%, and CaO 0.3-1.5wt%.
[0029] The NiCuZn-MgO composite material of the present application is prepared by the following method, comprising the following steps: S1, mixing the main components Fe2O3, ZnO, NiO, MgO, CuO and part of Bi2O3 in the additive by wet sand grinding to obtain a mixture A; S2, pre-calcining the mixed material A obtained in step S1 to obtain a pre-calcined material; S3, adding additives SiO2, CaO and the remaining part of Bi2O3 to the pre-burned material obtained in step S2, and performing secondary sand grinding to obtain a mixed material B; S4, adding a binder and a defoamer to the mixed material B obtained in step S3, stirring and mixing, and then spraying and granulating to obtain a granular material; S5, pressing the granular material obtained in step S4 into a green body through a mold; S6, sintering the green body obtained in step S5, and after sintering, rapidly cooling to obtain the NiCuZn-MgO composite material.
[0030] The NiCuZn-MgO composite material of the present application can be used in the field of soft magnetic ferrite materials.
[0031] The use of MgO to replace part of NiO in the present application can reduce the overall cost of nickel-zinc ferrite materials. An appropriate amount of MgO can act as a grain growth inhibitor, which helps to form a fine and uniform grain structure, thereby improving the high-frequency performance and mechanical strength of the material. It can also improve the sintering activity of the ferrite, which is conducive to obtaining better phase purity and higher density, thereby optimizing the magnetic properties; the addition of MgO can improve the sintering behavior of the ferrite, reduce the sintering temperature or shorten the sintering time, and is conducive to industrial large-scale production; the presence of MgO helps to increase the resistivity of the ferrite material, thereby reducing eddy current losses and improving device efficiency.
[0032] The present application selects Bi2O3, SiO2 and CaO as additives. Bi2O3, as a grain growth inhibitor, can effectively refine ferrite particles, thereby improving the high-frequency performance of the material; the addition of Bi2O3 can help reduce the sintering temperature of ferrite, and bismuth ions can promote the formation of liquid phase during the sintering process, thereby accelerating the sintering rate and improving the sintering activity; SiO2 can affect the sintering density and microstructure of ferrite, and the dielectric properties and mechanical properties of the material can be improved by adjusting its content; CaO can reduce grain boundary resistance and improve magnetic permeability, and can also inhibit the oxidation of grain boundaries, enhancing the oxidation resistance and stability of the material. Specific embodiments
[0033] Example 1 This embodiment provides a NiCuZn-MgO composite material, including a main component and an additive, wherein the main component includes the following components in weight percentage: 70wt% Fe2O3, 14wt% ZnO, 8wt% NiO, 4wt% MgO, and the balance is CuO; Based on the total weight of the main components, the additives include the following weight percentage components: 1.0wt% Bi2O3, 0.8wt% SiO2, and 0.8wt% CaO.
[0034] The preparation method of the NiCuZn-MgO composite material in this embodiment comprises the following steps: S1. The main components Fe2O3, ZnO, NiO, MgO, CuO and part of Bi2O3 in the additive are mixed by wet sand milling for 1.5 h to obtain a mixture A; S2, transferring the mixed material A into a sintering furnace for pre-burning at a temperature of 850°C for a pre-burning time of 3.5 hours to obtain a pre-burned material; S3, adding additives SiO2, CaO and the remaining part of Bi2O3 to the pre-burned material, and performing secondary sand grinding to obtain a mixture B, the particle size of the mixture B: D50 = 0.9 ± 0.1 μm; S4, adding a PVA binder having a solid content of 0.2 wt% of the mixed material B and a polydimethylsiloxane having a solid content of 0.1 wt% of the mixed material B to the mixed material B, and performing spray granulation to obtain a granular material; S5, pressing the granular material through a mold on a powder forming machine to obtain a circular ring-shaped body, the specification of the body is φ25×15×7.5mm; S6. The green body is transferred into a sintering furnace for sintering at a sintering temperature of 1080° C. for a sintering time of 5.5 h. After sintering, the green body is rapidly cooled to obtain the NiCuZn-MgO composite material.
[0035] Example 2-3 Example 2 The difference between this embodiment and embodiment 1 is that, when preparing the NiCuZn-MgO composite material, the sum of the weights of NiO and MgO accounts for 12 wt % of the main component, and the weight ratio of NiO to MgO is 1.2:1.
[0036] Example 3 The difference between this embodiment and embodiment 1 is that when preparing the NiCuZn-MgO composite material, the sum of the weights of NiO and MgO accounts for 12 wt % of the main component, and the weight ratio of NiO to MgO is 1.5:1.
[0037] Comparative Examples 1-5 Comparative Example 1 The difference between this comparative example and Example 3 is that when preparing the NiCuZn-MgO composite material, the sum of the weights of NiO and MgO accounts for 12 wt % of the main component, and the weight ratio of NiO to MgO is 1:1.
[0038] Comparative Example 2 The difference between this comparative example and Example 3 is that, when preparing the NiCuZn-MgO composite material, the sum of the weights of NiO and MgO accounts for 12 wt % of the main component, and the weight ratio of NiO to MgO is 2.5:1.
[0039] Comparative Example 3 The difference between this comparative example and Example 3 is that when preparing the NiCuZn-MgO composite material, an equal amount of NiO is used to replace MgO.
[0040] Comparative Example 4 The difference between this comparative example and Example 3 is that when preparing the NiCuZn-MgO composite material, all Bi2O3 is added in step S1.
[0041] Comparative Example 5 The difference between this comparative example and Example 3 is that, when preparing the NiCuZn-MgO composite material, Bi2O3 is not added in step S1, and all Bi2O3 is added in step S3.
[0042] The specific components of the NiCuZn-MgO composite materials prepared in Examples 1 to 3 of the present invention and Comparative Examples 1 to 5 are shown in Table 1.
[0043] Table 1 Embodiment 4-5 The difference between Example 4-5 and Example 3 is that the amounts of some components are changed when preparing the NiCuZn-MgO composite material. See Table 2 for the differences.
[0044] Table 2 Example 6 The difference between Example 6 and Example 3 is that in step S3 of this embodiment, a dispersant of 0.8% of the total weight of the main components is added, and the dispersant is mannitol, light calcium carbonate and sodium lauryl sulfate in a weight ratio of 1:5:1.
[0045] Step S3 is: S3, adding additives SiO2, CaO, dispersant and the remaining part of Bi2O3 to the pre-burned material, performing secondary sand grinding to obtain a mixture B, the particle size of the mixture B is: D50 = 0.9 ± 0.1 μm.
[0046] Example 7 The difference between Example 7 and Example 3 is that in step S3 of this embodiment, a dispersant of 0.8% of the total weight of the main components is added, and the dispersant is mannitol, light calcium carbonate and sodium lauryl sulfate in a weight ratio of 2:6:3.
[0047] Step S3 is: S3, adding additives SiO2, CaO, dispersant and the remaining part of Bi2O3 to the pre-burned material, performing secondary sand grinding to obtain a mixture B, the particle size of the mixture B is: D50 = 0.9 ± 0.1 μm.
[0048] Example 8 The difference between Example 8 and Example 3 is that in step S3 of this example, a dispersant of 0.8% of the total weight of the main components is added, and the dispersant is mannitol, light calcium carbonate and sodium lauryl sulfate in a weight ratio of 3:7:2.
[0049] Step S3 is: S3, adding additives SiO2, CaO, dispersant and the remaining part of Bi2O3 to the pre-burned material, performing secondary sand grinding to obtain a mixture B, the particle size of the mixture B is: D50 = 0.9 ± 0.1 μm.
[0050] Experimental testing The following performance tests were performed on the NiCuZn-MgO composite materials obtained in Examples 1-8 and Comparative Examples 1-5: Initial magnetic permeability μ i :Under the condition of number of turns N=20Ts, the initial magnetic permeability of the sample ring is tested with HP-4284A LCR tester; Saturation magnetic induction intensity Bs: Under the condition of turns N=20Ts, the saturation magnetic induction intensity Bs of the nickel-zinc ferrite core is tested using SY-8258 BH analyzer.
[0051] Test results The test results are shown in Table 3.
[0052] Table 3 Results Analysis From the data in Examples 1-3, Comparative Examples 1-3 and Table 3, it can be seen that the use of MgO to replace part of NiO in the present application can not only reduce the production cost, but also an appropriate amount of MgO can be used as a grain growth inhibitor, which is conducive to obtaining better phase purity and higher density, thereby ensuring the magnetic properties of the ferrite. The presence of MgO helps to increase the resistivity of the ferrite material, thereby reducing eddy current losses and improving device efficiency.
[0053] From the data of Example 3, Comparative Examples 4-5 and Table 3, it can be seen that in the present application, the main component and part of Bi2O3 are mixed and sand-milled for pre-sintering, and then all the additive parts including the remaining Bi2O3 are added for the second time. Adding Bi2O3 twice can significantly optimize the structure of high nickel zinc ferrite, make the grains more uniform, and significantly improve the density of nickel zinc ferrite, so that the nickel zinc ferrite obtains high strength.
[0054] Combining Examples 3-5 and the data in Table 3, it can be seen that when the weight ratio of NiO and MgO is 1.2-2:1, the comprehensive performance of the obtained NiCuZn-MgO composite material is better, and when the weight ratio of NiO and MgO is 1.5:1, the comprehensive performance of the obtained NiCuZn-MgO composite material is better.
[0055] Combining the data of Example 3, Examples 6-8 and Table 3, it can be seen that when 0.8% of the total weight of the dispersant is added during the secondary sand grinding, the weight ratio of the dispersant is (1-3): (5-7): (1-3) mannitol, light calcium carbonate and sodium dodecyl sulfate, and the obtained NiCuZn-MgO composite material has better comprehensive performance.
[0056] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.
Claims
1. A NiCuZn-MgO composite material, comprising a main component and an additive, characterized in that: The main components include the following weight percentage components: Fe2O3 66-72wt%, ZnO 13-16wt%, NiO 6-9wt%, MgO 3-6wt%, and the balance is CuO; Based on the total weight of the main component, the additive includes the following weight percentage components: Bi2O3 0.5-1.5wt%, SiO2 0.3-1.5wt%, CaO 0.3-1.5wt%.
2. The NiCuZn-MgO composite material according to claim 1, characterized in that: In the main component, the weight ratio of NiO to MgO is 1.2-2:
1.
3. The NiCuZn-MgO composite material according to claim 2, characterized in that: Among the main components, the weight ratio of NiO to MgO is 1.5:
1.
4. A method for preparing the NiCuZn-MgO composite material according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1, mixing the main components Fe2O3, ZnO, NiO, MgO, CuO and part of Bi2O3 in the additive by wet sand grinding to obtain a mixture A; S2, pre-calcining the mixed material A obtained in step S1 to obtain a pre-calcined material; S3, adding additives SiO2, CaO and the remaining part of Bi2O3 to the pre-burned material obtained in step S2, and performing secondary sand grinding to obtain a mixed material B; S4, adding a binder and a defoamer to the mixed material B obtained in step S3, stirring and mixing, and then spraying and granulating to obtain a granular material; S5, pressing the granular material obtained in step S4 into a green body by a mold; S6, sintering the green body obtained in step S5, and after sintering, rapidly cooling to obtain the NiCuZn-MgO composite material.
5. The method for preparing the NiCuZn-MgO composite material according to claim 4, characterized in that: Based on the total weight of the main components, the amount of Bi2O3 added in step S1 is 0.3-0.5wt%, and the sanding time is 1-2h.
6. The method for preparing the NiCuZn-MgO composite material according to claim 4, characterized in that: In step S2, the pre-firing temperature is 800-900° C., and the pre-firing time is 3-4 hours.
7. The method for preparing the NiCuZn-MgO composite material according to claim 4, characterized in that: In the step S3, a dispersant is added in an amount of 0.5-1.2% of the total weight of the main components.
8. The method for preparing the NiCuZn-MgO composite material according to claim 4, characterized in that: The dispersant includes mannitol, light calcium carbonate and sodium lauryl sulfate in a weight ratio of (1-3):(5-7):(1-3).
9. The method for preparing the NiCuZn-MgO composite material according to claim 4, characterized in that: After the secondary sand grinding in step S3, the particle size D50 of the mixture B is 0.9±0.1 μm.
10. The method for preparing the NiCuZn-MgO composite material according to claim 4, characterized in that: In step S6, the sintering temperature is 1050-1100° C., and the sintering time is 5-6 hours.
Citation Information
Patent Citations
Broadband high-strength heat-shock-resistant nickel-zinc ferrite magnetic core and preparation method thereof
CN115490507A
Ferrite material
CN1749211A
Magnetic material and coil part using the same
JP2002134312A
Cited By
NiCuZn ferrite material with high cut-off frequency and preparation method
CN122254876A